Thermodynamic description of the Al-Cu-Yb ternary system supported by first-principles calculations (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
Phase relationships of the ternary Al-Cu-Yb system have been assessed coupling with CALPHAD method and first-principles calculations, a self-consistent thermodynamic parameter was established based on the experimental and theoretical information. Most of the binary intermetallic phases, except Al3Yb, Al2Yb, Cu2Yb and Cu5Yb, are assumed to be zero solubility in the ternary system. Based on experimental data, eight ternary intermetallic compounds were taken into consideration in this system. Among them, three were treated as line compounds with large homogeneity ranges for Al and Cu. The others were treated as stoichiometric compounds. The calculated phase diagrams were in agreement with available experimental and theoretical data.